Predictors of low disease activity and clinical remission following belimumab treatment in systemic lupus erythematosus - Parodis, Ioannis (Rheumatology (Oxford), 2019)
OBJECTIVES: To identify predictors of low disease activity and clinical remission following belimumab treatment in SLE. METHODS: SLE patients who received belimumab 10 mg/kg (N = 563) in the BLISS-52 and BLISS-76 clinical trials were surveyed. The performance of baseline factors in predicting attainment of low disease activity (defined as Lupus Low Disease Activity State) or clinical remission [defined as clinical (c)SLEDAI-2K = 0] at week 52 from treatment initiation was evaluated using logistic regression. Organ damage was assessed using the SLICC/ACR Damage Index (SDI). RESULTS: We demonstrated a negative impact of established organ damage on attainment of Lupus Low Disease Activity State [SDI > 0; odds ratio (OR): 0.44; 95% CI 0.22, 0.90; P = 0.024] and the primary Lupus Low Disease Activity State condition, i.e. SLEDAI-2K ⩽ 4 with no renal activity, pleurisy, pericarditis or fever (SDI > 1; OR: 0.46; 95% CI 0.27, 0.77; P = 0.004); cognitive impairment/psychosis was found to mainly account for the latter association. Baseline SDI scores > 1 predicted failure to attain cSLEDAI-2K = 0 (OR: 0.53; 95% CI 0.30, 0.94; P = 0.030), with cutaneous damage mainly driving this association. Anti–dsDNA positivity increased (OR: 1.82; 95% CI 1.08, 3.06; P = 0.025) and cardiovascular damage reduced (OR: 0.13; 95% CI 0.02, 0.97; P = 0.047) the probability of attaining cSLEDAI-2K = 0 along with a daily prednisone equivalent intake restricted to ⩽7.5 mg. CONCLUSION: Belimumab might be expected to be more efficacious in inducing low disease activity and clinical remission in SLE patients with limited or no organ damage accrued prior to treatment initiation. Patients with positive anti–dsDNA titres might be more likely to achieve clinical remission along with limited or no CS use.